Alternative supplement for enhancement of reproductive health and metabolic profile among perimenopausal women: a novel role of Nigella sativa - Abd Latiff, Latiffah; Parhizkar, Saadat; Dollah, Mohamad Aziz; Syed Hassan, Syed Tajuddin (Mashhad University of Medical Sciences, 2015)
Objective(s): The aim of this open label crossover study was to investigate the effects of Nigella sativa on reproductive health and metabolic profile of perimenopausal women in Rawang, Malaysia.